Safety and cost analysis of early discharge following percutaneous coronary intervention for acute coronary syndrome in patients with diabetes mellitus. Issue 8 (August 2019) - Li, Shihong; Li, Zhizhong; Hou, Xuejian; Sun, Junping; Kang, Lihui; Cheng, Yutong; Tao, Ying; Li, Zhao; Chen, Xuanzu; Zhang, Donghua; Yan, Xianliang; Wang, Su; et al.
Objective: To evaluate the safety and cost of early discharge compared with ordinary discharge in patients with diabetes mellitus (DM) following percutaneous coronary intervention (PCI) for acute coronary syndrome. Methods: We performed a retrospective analysis of prospectively collected data from 474 patients with DM who were discharged from hospital following PCI at a regional center between 2012 and 2015. Results: A total of 192 patients (40.5%) were included in the early discharge group and 282 patients (59.5%) were included in the ordinary group. Mortality and morbidity after PCI were recorded. Kaplan–Meier analysis showed similar prognosis between the two groups at 30 days and at 1 year after discharge. However, hospitalization expenses for the regular discharge group were significantly higher than those of the early discharge group (RMB65, 750 vs. RMB50, 983). Conclusion: Our findings demonstrate that early discharge of patients with DM following PCI for acute coronary syndrome is safe compared with ordinary discharge, and may reduce hospitalization costs.